Empowerment of Green Economy through Used Cooking Oil Processing and Improvement of English Language Skills Using Wordwall.net Media for Teachers - Novianti, Rini; Ryandini, Elda Yulia; Sulistyowati, Eny; Shobichah, Hidayatus (Jurnal Abmas Negeri (JAGRI), 2025)
Empowering the green economy through training on used cooking oil (UCO) waste processing with economic value and improving English using Wordwall.net application as learning media was a form of community service of STIE IBMT lecturers to teachers of the Nurul Alim Education Foundation Surabaya. This program was carried out because of the important issue of environmental damage as a result of unwise economic activities and human consumption, so that the empowerment of the green economy was present as a sustainable development solution that pays attention to environmental sustainability. This program was aimed to increase partner’s knowledge about the concept of green economy in theory and practice such as how to make aromatherapy candles from used cooking oil and using the Wordwall.net application as an interesting English learning media. The implementation method began with a situation and need analysis, preparation of materials (green economy, used cooking oil processing, and wordwall.net), training, and evaluation. The program involved 17 teachers of Nurul Alim. It went smoothly and successfully, as evidence by the participant's enthusiasm of each session. Evaluation results showed an increase in participants’ knowledge about empowerment of green economy, from a pre test score of 48% to 84% in the pos-test.